Comparison of Sharia Business Law Opinions on Fine Sanctions For Late Payment of Installments in Sharia Financial Institutions - Hidayatullah, Muhammad Syarif; Ragil Rahmatullah Nurhakim (Bilancia: Jurnal Studi Ilmu Syariah dan Hukum, 2023)
Islamic Financial Institutions are financial institutions whose operations are based on Sharia principles or Islamic legal rules in the financial transactions that are carried out. Closely to conventional financial institutions, fines for late payment of installments by customers are also applied by Islamic financial institutions whose legality refers to the DSN-MUI fatwa on sanctions against capable customers who delay payments. The issue of fines eventually creates problems and debates on its legality and relevance to sharia principles. This research aimed to compare sharia business law opinions on issues of fines for late installment payments at Islamic financial institutions. The research method employed was normative legal research with a comparative approach. The research results revealed the difference of opinions on the existence and legal status of these fines in Islamic financial institutions. Leastwise, there are two legal opinions: (1) it is permissible on condition that fines are only given to capable customers who delay payments (under specific criteria, not absolute permissibility) and that fines must be designated as social funds. Meanwhile, (2) disapproving opinion to assume that this fine is similar to usury; hence, it is forbidden.